2021
DOI: 10.1111/ajt.16405
|View full text |Cite
|
Sign up to set email alerts
|

CD69+ resident memory T cells are associated with graft-versus-host disease in intestinal transplantation

Abstract: Graft-versus-host disease (GvHD) is a common, morbid complication after intestinal transplantation (ITx) with poorly understood pathophysiology. Resident memory T cells (T RM ) are a recently described CD69+ memory T cell subset localizing to peripheral tissue. We observed that T effector memory cells (T EM ) in the blood increase during GvHD and hypothesized that they derive from donor graft CD69+T RM migrating into host blood and tissue. To probe this hypothesis, graft and blood lymphocytes from 10 ITx patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…Longitudinal analysis of donor T cell chimerism in recipient peripheral blood mononuclear cells (PBMCs) (Figure 1A, Figure S1) clearly revealed donor T cell macrochimerism (>4%) with a predominantly expressed effector memory phenotype in both CD4 and CD8 T cell (Figure 1B,C) in patients with GVHD (Pt62, Pt143) as reported in intestinal transplantation associated GVHD study, 4 whereas the non‐GVHD patients did not show donor T cell macrochimerism, which agrees with a previous report 5 …”
Section: Case Reportssupporting
confidence: 60%
See 2 more Smart Citations
“…Longitudinal analysis of donor T cell chimerism in recipient peripheral blood mononuclear cells (PBMCs) (Figure 1A, Figure S1) clearly revealed donor T cell macrochimerism (>4%) with a predominantly expressed effector memory phenotype in both CD4 and CD8 T cell (Figure 1B,C) in patients with GVHD (Pt62, Pt143) as reported in intestinal transplantation associated GVHD study, 4 whereas the non‐GVHD patients did not show donor T cell macrochimerism, which agrees with a previous report 5 …”
Section: Case Reportssupporting
confidence: 60%
“…Longitudinal analysis of donor T cell chimerism in recipient peripheral blood mononuclear cells (PBMCs) (Figure 1A, Figure S1) clearly revealed donor T cell macrochimerism (>4%) with a predominantly expressed effector memory phenotype in both CD4 and CD8 T cell (Figure 1B,C) in patients with GVHD (Pt62, Pt143) as reported in intestinal transplantation associated GVHD study, 4 whereas the non-GVHD patients did not show donor T cell macrochimerism, which agrees with a previous report. 5 Pt143 showed significant donor T cell macrochimerism at postoperation day (POD) 31 prior to GVHD diagnosis (POD32), it maintained at a peak level during the disease progression (POD32-36), declined rapidly during the recovery period, and disappeared when the disease resolved (at POD55) (Figure 1A).…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Patients underwent routine loop ileostomy creation at the time of transplant for post-transplant monitoring, with planned restoration of intestinal continuity and closure of the ileostomy three to six months later. Post-transplant monitoring included endoscopy and biopsy twice weekly for the first 6 weeks, weekly until month three, biweekly until month six, and monthly thereafter, as previously described [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have demonstrated that donor-derived clones in native colon mucosa of selected ITx recipients with typical features of GVHD have a CD69 + resident memory T-cell phenotype. 17 Complimentary to this work, we herein report our clinical GVHD experience after ITx with a heightened focus on risks for occurrence compared with ITx recipients not developing GVHD.…”
Section: Introductionmentioning
confidence: 99%